Proteomic screening identifies calreticulin as a miR-27a direct target repressing MHC class I cell surface exposure in colorectal cancer - Colangelo, T (Cell Death Dis, 2016)
Impairment of the immune response and aberrant expression of microRNAs are emerging hallmarks of tumour initiation/progression, in addition to driver gene mutations and epigenetic modifications. We performed a preliminary survey of independent adenoma and colorectal cancer (CRC) miRnoma data sets and, among the most dysregulated miRNAs, we selected miR-27a and disclosed that it is already upregulated in adenoma and further increases during the evolution to adenocarcinoma. To identify novel genes and pathways regulated by this miRNA, we employed a differential 2DE-DIGE proteome analysis. We showed that miR-27a modulates a group of proteins involved in MHC class I cell surface exposure and, mechanistically, demonstrated that calreticulin is a miR-27a direct target responsible for most downstream effects in epistasis experiments. In vitro miR-27a affected cell proliferation and angiogenesis; mouse xenografts of human CRC cell lines expressing different miR-27a levels confirmed the protein variations and recapitulated the cell growth and apoptosis effects. In vivo miR-27a inversely correlated with MHC class I molecules and calreticulin expression, CD8(+) T cells infiltration and cytotoxic activity (LAMP-1 exposure and perforin release). Tumours with high miR-27a, low calreticulin and CD8(+) T cells' infiltration were associated with distant metastasis and poor prognosis. Our data demonstrate that miR-27a acts as an oncomiRNA, represses MHC class I expression through calreticulin downregulation and affects tumour progression. These results may pave the way for better diagnosis, patient stratification and novel therapeutic approaches.